2009
DOI: 10.1016/j.micres.2006.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation and quantification of stressed Escherichia coli K12 NCTC8797 in water samples

Abstract: The aim of this study was to investigate the impact on numbers of using different media for the enumeration of Escherichia coli subjected to stress, and to evaluate the use of different resuscitation methods on bacterial numbers. E. coli was subjected to heat stress by exposure to 55 degrees C for 1h or to light-induced oxidative stress by exposure to artificial light for up to 8h in the presence of methylene blue. In both cases, the bacterial counts on selective media were below the limits of detection wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…For the pilot study (Additional file 1: Figure S4A), the MPN assays (adapted from [140][141][142][143][144]) were performed on each GIT section (stomach, three sub-sections of the small intestine, cecum, and colon) from five mice fitted with functional tail cups and five control mice. The growth medium was brain heart infusion broth (Bacto BHI, #237500, Becton Dickinson, Franklin Lakes, NJ, USA), prepared in ultrapure water (Milli-Q), sterilized by autoclaving, allowed to cool to room temperature, and supplemented with 1.0 mg/L vitamin K 1 (#L10575, Alfa Aesar, Haverhill, MA, USA), 5 mg/L hematin (#H3281, Sigma-Aldrich St. Louis, MO, USA), and 0.25 g/L L-cysteine (#168149, Sigma-Aldrich).…”
Section: Most Probable Number (Mpn) Assaymentioning
confidence: 99%
“…For the pilot study (Additional file 1: Figure S4A), the MPN assays (adapted from [140][141][142][143][144]) were performed on each GIT section (stomach, three sub-sections of the small intestine, cecum, and colon) from five mice fitted with functional tail cups and five control mice. The growth medium was brain heart infusion broth (Bacto BHI, #237500, Becton Dickinson, Franklin Lakes, NJ, USA), prepared in ultrapure water (Milli-Q), sterilized by autoclaving, allowed to cool to room temperature, and supplemented with 1.0 mg/L vitamin K 1 (#L10575, Alfa Aesar, Haverhill, MA, USA), 5 mg/L hematin (#H3281, Sigma-Aldrich St. Louis, MO, USA), and 0.25 g/L L-cysteine (#168149, Sigma-Aldrich).…”
Section: Most Probable Number (Mpn) Assaymentioning
confidence: 99%
“…Higgins et al, (2007) suggested that the increase in densities was due to the resuscitation or reactivation of bacteria that had become temporarily nonculturable. This phenomena of reactivation has also been documented in matrixes such as water (Lim 1995, Momba 2002,Ozkanca 2009 These studies suggest that bacteria subjected to heat stress enter into a protective state where they are not able to grow on standard microbiological media. However, the bacteria are able to recover from this state over time as conditions become favorable for growth.…”
Section: Introductionmentioning
confidence: 72%
“…Gram negative pathogens such as Salmonella and other Enterobacteriaceae are sensitive to freezing injury and there is also some mortality of mesophilic Vibrios (30). Various stress factors may lead to the generation of a dormant or viable but non-culturable state in the bacterial cells which direct bacteria to be unable to produce observable colonies when cultured on selective and non-selective agar media (31). Despite this condition, these bacteria possess the ability to cause disease in suitable conditions (32,33,34).…”
Section: Resultsmentioning
confidence: 99%